Determinants of revenue efficiency of Islamic banks: empirical evidence from the Southeast Asian countries - Sufian, Fadzlan; Kamarudin, Fakarudin (Emerald Group Publishing, 2015)
Purpose: The purpose of this paper is to examine the revenue efficiency of Islamic banks in the Southeast Asian countries. Specifically, the empirical analysis comprises Islamic banks operating in Malaysia, Indonesia and Brunei. This paper also seeks to investigate the potential internal (bank-specific) and external (macroeconomic and industry-specific) factors which influence the revenue efficiency of Islamic banks operating in Southeast Asian countries. Design/methodology/approach: This paper used a whole gamut of domestic and foreign Islamic banks operating in Southeast Asian countries, namely, Malaysia, Indonesia and Brunei during the period of 2006-2011. The level of revenue efficiency is computed by using the data envelopment analysis (DEA) method. Following the procedure set in Banker and Natarajan (2008) and Gujarati (2002), this paper use a panel regression analysis framework based on the ordinary least square and generalized least square methods to examine the potential determinants of revenue efficiency of the Islamic banks in the sample. In addition, this paper also use a battery of parametric (t-test) and non-parametric (Mann–Whitney [Wilcoxon] and Kruskall–Wallis) tests to examine the difference in the revenue efficiency of the domestic and foreign Islamic banks. Findings: The results indicate that the level of revenue efficiency on the domestic Islamic banks is higher compared to that of their foreign Islamic bank counterparts. The empirical findings seem to suggest that revenue efficiency has greater influence on the profit efficiency levels. It was found that the bank size, asset quality, capitalization, liquidity and management quality significantly influence the revenue efficiency of domestic Islamic banks operating in Malaysia, Indonesia and Brunei during the period under study. Research limitations/implications: Due to its limitations, the present study may be extended in variety of ways. First, if information on input prices is available, further analysis could be performed to investigate the cost, technical and allocative efficiency. Second, interested researchers may apply the Malmquist Productivity Index method to examine the sources of total factor productivity changes of Islamic banks operating in the ASEAN countries. Third, to obtain more robust results, empirical findings from the present study could be compared to the results derived from improved statistical methods, i.e. Bootstrap DEA. Practical implications: The empirical findings of this paper clearly call for regulators and decision-makers to review the revenue efficiency of banks operating in Malaysia, Indonesia and Brunei Islamic banking sectors. The results could also provide better information and guidance to the managers of Islamic banks, as they need to have a clear understanding on the impact of revenue efficiency on the performance of their banks. The empirical findings of this paper may also have implications for investors whose main focus is to gain higher profit from their investments. Originality/value: The paper is the first to provide empirical evidence on the determinants of revenue, cost and profit efficiency of Islamic banks operating in Southeast Asian countries.